2006
DOI: 10.1002/nbm.1062
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of treatment effects in Alzheimer's and other neurodegenerative diseases by MRI and MRS

Abstract: Neurodegeneration refers to a large clinically and pathologically heterogeneous disease entity associated with slowly progressive neuronal loss in different anatomical and functional systems of the brain. Neurodegenerative diseases often affect cognition, e.g. Alzheimer's disease (AD), dementia with Lewy bodies and vascular dementia, or different aspects of the motor system, e.g., amyotrophic lateral sclerosis, Parkinson's disease and ataxic disorders. Owing to increasing knowledge about the mechanisms leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 108 publications
0
48
0
Order By: Relevance
“…Elevated mI in MCI patients might be associated with glial activation and inflammation in the pathology of AD. 6,10,20 Therefore, an elevated mI followed later by a decreased NAA level might imply that glial activation preceded neuronal loss or dysfunction in MCI. 10 Furthermore, we found that ADC values increased incrementally among the controls, MCI and AD patients.…”
Section: Discussionmentioning
confidence: 98%
“…Elevated mI in MCI patients might be associated with glial activation and inflammation in the pathology of AD. 6,10,20 Therefore, an elevated mI followed later by a decreased NAA level might imply that glial activation preceded neuronal loss or dysfunction in MCI. 10 Furthermore, we found that ADC values increased incrementally among the controls, MCI and AD patients.…”
Section: Discussionmentioning
confidence: 98%
“…We used independent-samples t-test with a 5% significance level to (4,8,34) f,m,m +/+/− +/+/+ C (12) f − + D (14) f − + E (19,20,22,28) f compare means in the two groups. The Pearson correlation coefficient was used to analyze associations between continuous variables.…”
Section: Statisticsmentioning
confidence: 99%
“…Proton magnetic resonance spectroscopy (MRS) [18][19][20][21] has proved useful in investigating neurodegenerative diseases, but has so far only been performed in complicated forms of HSP [22,23]. Our hypothesis was that SPG4-HSP leads to cerebral changes reflecting a pathological process involving specific parts of the brain, among them motor cortex and frontal white matter.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…1 H-MRS has been demonstrated to be highly specific and sensitive to the diagnosis of Alzheimer's dementia (AD) [15]. Reduction in NAA is the most frequent 1 H-MRS finding in AD [84,85]. Single Voxel 1 H-MRS studies have consistently found reductions in NAA/Cr ratio in the hippocampal formation [85] as well as other temporal regions [86] and the posterior cingulate gyrus [87].…”
Section: Neurodegenerative Diseases (Alzheimer/parkinson)mentioning
confidence: 99%